Elevated serum DAND5 is associated with metastasis and predicts poor prognosis in colorectal cancer. Issue 5 (August 2017) - Miao, Xiaofei; Zhang, Ye; Sun, Jialin; Cui, Songkui; Meng, Qingyang; Zhu, Kuiyu; Hu, Xingqian; Wang, Tong
Background: The biologic and clinical significance of DAND5 remains unknown in colorectal cancer (CRC). Objective: Herein, we investigated the function of DAND5 and evaluated its clinical significance in both serum and matched primary tumors in patients with CRC. Methods: The role of DAND5 was explored in CRC cells and clinical significance of DAND5 was investigated in CRC patients ( n  = 217) and healthy controls ( n  = 63). Results: Knockdown of DAND5 significantly decreased CRC cell proliferation, migration and invasion partly associated with epithelial–mesenchymal transition phenotype. Serum DAND5 levels in CRC were significantly higher than in normal controls and accurately distinguished CRC from healthy subjects. High serum DAND5 levels were significantly correlated with tumor differentiation, large tumor size, advanced Tumor Node Metastasis (TNM) stage, lymph node and liver metastasis, high carcinoembryonic antigen level, recurrence, poor overall and disease-free survival. Serum DAND5 level, together with lymph node metastasis, were independent prognostic factors for CRC patients. High DAND5 protein expression in CRC tissues was increased according to TNM stage. A significant positive correlation existed between serum DAND5 levels and matched DAND5 expression in CRC tissues. Conclusion: Our data provide novel evidence for the clinical significance of DAND5 as a potential biomarker for CRC prognosis.